Dependent Elements of Biadditive Mappings on Semiprime Rings - Majeed, Abdul-Rahman H; Mahmood, Auday Hekmat (Al-Nahrain Journal of Science, 2018)
In this paper; we introduce the concepts of dependent element and free action associated to a biadditive mapping. We shall investigate some properties of dependent element of various mapping related to Bicentralizer on a semiprimerings. Also we identify various situations where these maps are free action.